2004
DOI: 10.1111/j.0009-9163.2004.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

De novo germline mutation in the serine–threonine kinase STK11/LKB1 gene associated with Peutz–Jeghers syndrome

Abstract: Peutz-Jeghers syndrome (PJS) is an autosomal dominant disease, characterized phenotypically by mucocutaneous pigmentation and hamartomatous polyposis. Affected patients are at an increased risk of developing gastrointestinal and other malignancies. Mutations in the STK11/LKB1 (LKB1) gene, which encodes for a serine-threonine kinase, have been identified as a genetic cause of PJS. Molecular analysis of the LKB1 gene in a simplex case of PJS revealed a substitution of cytosine (C) for guanine (G) at codon 246 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Interestingly, the observation of haploinsufficiency of Lkb1 in myofibroblast differentiation as measured by SMA reporter activity (Fig. 4D) resembles the situation in vivo in heterozygote PJS patients and mice, in which haploinsufficiency of Lkb1 leads to polyposis (Hernan et al, 2004;Jishage et al, 2002;Rossi et al, 2002). Thus, the role of Lkb1 in the differentiation of SM22-positive cells that was investigated here suggests that aberrant differentiation of the SM22-positive cell lineage in mice underlies polyposis.…”
Section: Role Of Lkb1 In Myofibroblast and Smc Differentiationsupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, the observation of haploinsufficiency of Lkb1 in myofibroblast differentiation as measured by SMA reporter activity (Fig. 4D) resembles the situation in vivo in heterozygote PJS patients and mice, in which haploinsufficiency of Lkb1 leads to polyposis (Hernan et al, 2004;Jishage et al, 2002;Rossi et al, 2002). Thus, the role of Lkb1 in the differentiation of SM22-positive cells that was investigated here suggests that aberrant differentiation of the SM22-positive cell lineage in mice underlies polyposis.…”
Section: Role Of Lkb1 In Myofibroblast and Smc Differentiationsupporting
confidence: 58%
“…A smaller, but still significant, decrease in (CAGA) 12 -luc activity was also noted in AdCre-infected Lkb1 lox/+ MEFs (16%; P=0.0014) (Fig. 1A, lox/+ bars), demonstrating haploinsufficiency of Lkb1 in this model and indicating similarity in this regard to the tumor-suppressor function of Lkb1 (Hernan et al, 2004;Jishage et al, 2002;Miyoshi et al, 2002;Rossi et al, 2002).…”
Section: Lkb1 Modulates Smad-dependent Transcriptionmentioning
confidence: 54%
“…Secondly, our findings suggest that MEK and RAF inhibitors may be useful in the treatment of PJS by activating LKB1 when an intact LKB1 allele is present. Recent studies have shown that haploinsufficiency of LKB1 is sufficient for the formation of hamartomatous polyps in mouse models, and there is evidence that a wild-type allele of LKB1 can be found in the harmatomatous polyps from PJS patients (Hernan et al, 2004). Lastly, in addition to direct AMPK activators, strategies based on modulating post-translational modifications of LKB1, such as MEK and RAF inhibitors, that activate AMPK indirectly, could also be considered for the treatment of metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we proposed that PJS polyps are not premalignant and are a signpost to the malignant condition, not its direct obligate histological precursor (54). Polyps both in patients (30,47) as well as in murine models (9,57,85,92,127) retain the wild-type allele. Moreover, polyps removed from patients are polyclonal (30).…”
Section: B Polyp Developmentmentioning
confidence: 99%